Age-associated epigenetic change in chimpanzees and humans. (9th November 2020) - Guevara, Elaine E.; Lawler, Richard R.; Staes, Nicky; White, Cassandra M.; Sherwood, Chet C.; Ely, John J.; Hopkins, William D.; Bradley, Brenda J.
Abstract : Methylation levels have been shown to change with age at sites across the human genome. Change at some of these sites is so consistent across individuals that it can be used as an 'epigenetic clock' to predict an individual's chronological age to within a few years. Here, we examined how the pattern of epigenetic ageing in chimpanzees compares with humans. We profiled genome-wide blood methylation levels by microarray for 113 samples from 83 chimpanzees aged 1–58 years (26 chimpanzees were sampled at multiple ages during their lifespan). Many sites (greater than 65 000) showed significant change in methylation with age and around one-third (32%) of these overlap with sites showing significant age-related change in humans. At over 80% of sites showing age-related change in both species, chimpanzees displayed a significantly faster rate of age-related change in methylation than humans. We also built a chimpanzee-specific epigenetic clock that predicted age in our test dataset with a median absolute deviation from known age of only 2.4 years. However, our chimpanzee clock showed little overlap with previously constructed human clocks. Methylation at CpGs comprising our chimpanzee clock showed moderate heritability. Although the use of a human microarray for profiling chimpanzees biases our results towards regions with shared genomic sequence between the species, nevertheless, our results indicate that there is considerable conservation in epigenetic ageing between chimpanzees and humans, but also substantial divergence in both rate and genomic distribution of ageing-associated sites. This article is part of the theme issue 'Evolution of the primate ageing process'.